Promoting resilience responding to adversity, vulnerability, and loss - Thompson, Neil 1955-; Cox, Gerry R. (Routledge, 2020)
"Promoting Resilience offers a fresh perspective that views resilience through a sociological lens, emphasizing the significance of loss issues and highlighting a range of practice implications across a wide range of fields. Drawing on the expertise of a wide range of contributors, the book provides a solid foundation for developing a fuller and more holistic picture of the many challenges associated with promoting resilience. Chapters present a range of sociological perspectives that cast light on trauma and vulnerability. Combining theoretical richness with practical insights, chapter authors bring a sociological lens to enrich understanding of loss and adversity. This volume offers a bedrock of understanding for students, clinicians, and researchers who want to extend and deepen their knowledge of the sociological aspects of overcoming life challenges."--Provided by publisher.